MANAJEMEN PERENCANAAN DAN PENGELOLAAN KEUANGAN (BOS) SEKOLAH DASAR DI KOTA PADANG - Risdal Yosli; Kasman Rukun; Muhammad Giatman (JURNAL KEPEMIMPINAN DAN PENGURUSAN SEKOLAH, 2020)
School financial management or financial School Operational Assistance is carried out directly by the school, but is guided and supervised by the education office. The authorized school, called School Based Management, manages school finances based on BOS technical guidelines and technical guidelines from the city BOS manager. Financial management is carried out through the stages of planning, realization and reporting. The smooth management of school finances depends on good management, starting from the decision maker to the lowest level, namely the school. The smoothness of financial management has an impact on other fields in the administration of education.